Effectiveness of the IMPETUS protocol in patients with chronic tinnitus: a randomized and controlled study - Cerejeira, Rui (2010)
Introduction: Tinnitus is a major symptom in medical daily practice with a prevalence in general population estimated to be around 1O to 15%.  Nearly 2O% of these persons report significant impact of tinnitus in their lives with interference in personal, professional and social functioning, forcing them to search health care advice. The usual specialized management, as done by otolaryngologists, does not include a psychosomatic evaluation in the initial assessment, as there is not enough scientific evidence to justify such intervention.Hypothesis: Chronic tinnitus sufferers, with great impact  on quality of life, will benefit from a combined interdisciplinary approach with both otolaryngological and psychosomatic inter- ventions (IMPETUS Protocol).Methods: Portuguese version of Mini-TQ (Mini-TQ-pv) and Visual Analog Scale (VAS), from O to 1O, were administered consecutively to the first 55 patients assessed for the first time with chronic tinnitus (> 6 mo) in the Tinnitus Outpatient Clinic of the Otolaryngology Department. Patients with Mini-TQ-pv scores above 7I24 were randomly divided in two branches - one group was referred to Psychosomatic evaluation while the other kept the exclusive Otolaryngological intervention.For comparison of quantitative variables in the same subgroup of the sample it was used the non parametric test of Wilcoxon.Results: The sample consisted of 55 patients, 34 women and 21 men. Mean age was 62,18 years (range, 38-82 yr). Initial Mini-TQ-pv and VAS scores were respectively 14,65±5,595 and 5,93±1,73O.  In  the  group  of  patients  submitted  to  the  combined  interdisciplinary  (otolaryngological  and  psychosomatic) approach there was a statistically significative reduction of the Mini-TQ-pv scores (16,74±4,7O3 to 14,O7±5,158, p<O,OO1) and VAS scores (6,15±1,791 to 5,37±1,69O, p=O,O17) after one year of follow up. The other groups did not show statistical significance results.Conclusions: This study showed that patients submitted to the IMPETUS Protocol have better outcomes when compared to patients treated with exclusive otolaryngological intervention.